(untitled) (Research, Society and Development, 2022)
Objective: The present work aims to explain about myelomeningocele and compare its therapeutic options. Methodology: A bibliographic review research was carried out, based on the PubMed search platform, in which a filtering process was carried out to select and exclude sources. Results and discussion: Myelomeningocele is the main central nervous system anomaly that may have fetal surgery as a therapeutic option. MMC brings with it several postnatal consequences, such as hydrocephalus and paraplegia, and directly affects morbidity and mortality. It is considered a multifactorial pathology, which has several risk factors associated with its origin, such as genetic alterations and folate deficiency. MMC can manifest in all body systems and the severity varies depending on the location of the injury. The diagnosis of MMC is made through laboratory and imaging tests. There are three therapeutic options for a myelomeningocele: termination of pregnancy, intrauterine repair and postnatal repair. Fetal surgery can be performed by the open method or by fetoscope. Conclusion: All therapeutic options have their risks and benefits, it is up to the health team, together with the family, to decide the best alternative.